Endometriosis. Introduction. - Benavente Lozada, Benjamin (2015)
Endometriosis is characterized by the presence of functioning endometrial tissue outside its normal situation, but usually confined to the pelvis in the region of the ovaries, utero-sacral ligaments, pouch of Douglas or utero-vesical peritoneum. It must be understood why the endometrial tissue proliferates, grows and works (usually bleeds) in a location outside the womb.